Mothers and Fathers self esteem and parenting styles: importance for family primary health prevention - Pires, Mónica (2012)
Parenting styles (PS), inferred family climate and its relation to child’s development, have been associated with contextual and individual variables, but only recently family studies included several members. Study’s main objective is to analyse PS couple’s concordance and the influence of self-esteem on PS mainly adopted. For 95 Portuguese couples conveniently selected, no differences were found between mothers’ and fathers’ PS and Self-esteem. Correlations were found for both parents, between permissiveness, authoritarian and negative self-esteem, but only fathers authoritativeness correlates to negative self-esteem (r ¼ 0.21, p ¼ 0.05). Results showed that gender and education level predicts authoritative style [F(2,170) ¼ 6.75, p ¼ 0.002]. Results showed that parents resources such as negative self-esteem and lower academic level exerts an effect on authoritarian and permissive PS, stressing the importance of primary prevention health level to work on parents’ wellbeing and parenting skills such as responsiveness and monitoring availability in rearing their children in a balanced way.